Defensins and the dynamic genome: What we can learn from structural variation at human chromosome band 8p23.1 - Hollox, Edward J.; Barber, John C.K.; Brookes, Anthony J.; Armour, John A.L.

(untitled) (Genome Research, 2008)
Over the past four years, genome-wide studies have uncovered numerous examples of structural variation in the human genome. This includes structural variation that changes copy number, such as deletion and duplication, and structural variation that does not change copy number, such as orientation and positional polymorphism. One region that contains all these types of variation spans the chromosome band 8p23.1. This region has been studied in some depth, and the focus of this review is to examine our current understanding of the variation of this region. We also consider whether this region is a good model for other structurally variable regions in the genome and what the implications of this variation are for clinical studies. Finally, we discuss the bioinformatics challenges raised, discuss the evolution of the region, and suggest some future priorities for structural variation research.